Impact of green credit on high-efficiency utilization of energy in China considering environmental constraints - Song, Malin; Xie, Qianjiao; Shen, Zhiyang (Energy policy, 2021)
Maintaining steady economic growth while considering environmental protection and achieving high-efficiency energy utilization is a challenge that China is' increasingly facing in the new normal. This study employs the super-efficiency data envelopment analysis and spatial econometric model to analyze energy utilization efficiency against the backdrop of environmental constraints. It uses China's inter-provincial panel data from 2007 to 2017 to examine the impact of green finance on high-efficiency utilization of energy. China's energy efficiency utilization shows an upward trend overall, but the utilization level is low. Energy efficiency utilization levels in the east, middle, and west show a declining gradient change. Green credit, credit scale, environmental regulation, technological progress, and industrial structure have a significant role in promoting high-efficiency utilization of energy. China's regional high-efficiency utilization of energy has an apparent spatial effect. Green credit, environmental regulation, technological progress, and industrial structure have a certain influence on the regional high-efficiency utilization of energy, but the influence of the credit scale is not apparent. Therefore, from the perspective of environmental constraints, green credit has a positive impact on high-efficiency utilization of energy in China. •Super-efficiency data envelopment analysis and spatial econometric model are used.•Green credit is an important tool for green finance.•China's energy efficiency utilization is low, but on the rise.•Green credit has a significant role in promoting high-efficiency utilization of energy.•China's regional high-efficiency utilization of energy has an apparent spatial effect.